Determination of argon fluoride (ArF) excimer laser system and materials diagnosis - Salleh, Mohd Hazimin Mohd; Bidin, Noriah (Penerbit Universiti Sains Malaysia, 2004)
The growing interest in precise fabrication of micro and nano-structures such as optical component, lenses, sensor and devices makes the conventional approach no longer satisfactory for micro scale structure. Now, nano-technology has a big potential to revolutionize everything from medicine, industrial manufacturing and to computer within a few decades.